Fabrication of Screen-Printed Electrodes Modified by Hydrothermal MnO2 Microflowers and Carbon for Electrochemical Sensors in Copper Ions Detection - Huyen T. T. Nguyen; Nam T. H. Chu; Hang T. T. Le (Journal of Chemistry)
Porous MnO2 microflowers with a hexagonal crystalline structure were facilely prepared at a low hydrothermal temperature of 90°C, without using any template or capping agent. The as-prepared MnO2 only presented an excellent detection ability for copper (II) by a square wave anodic stripping voltammetry in the presence of super P carbon black as conducting agent, and Nafion as binder. In the present work, to evaluate the detection ability of copper (II) in the MnO2 microflowers, chips of screen-printed electrodes (SPEs) having a polyurethane substrate, a silver working electrode, a carbon counter electrode, and a silver pseudoelectrode, were designed. Then, the SPEs chips were modified with MnO2 microflowers and/or super P carbon and used as electrochemical sensors for the detection of copper (II) present in water sources. From the measured results, the fabricated sensors with excellent copper detection in a linear range from 0.625 nM to 15 nM (R2 = 0.9737), and a low detection limit (0.5 nM), high sensitivity (214.05 μA/cm2 nM), and rapid response (180 s) demonstrated high application potential for electrochemical sensors in the detection of copper in water resources.